EXPLORING THE INFLUENCE OF RESILIENCE AND CAREER ORIENTATION ON THE CAREER READINESS EXPERIENCES OF TRAINEES AT LKP ANANDA PERKASA MULIA - Rahman, Muhammad (BAIK Publishers, 2025)
This qualitative study explores how resilience and career orientation influence the career readiness experiences of trainees at LKP Ananda Perkasa Mulia. Career readiness is vital for successful transition from vocational training to employment, yet the psychological factors supporting readiness are understudied in vocational contexts. Data were collected through in-depth interviews and analyzed using thematic analysis to capture trainees’ coping strategies, motivation, and career goal-setting behaviors.Findings reveal that resilience enables trainees to overcome challenges, maintain motivation, and adapt positively to setbacks, while career orientation provides clear direction and purpose in career planning. The interplay of these factors cultivates a comprehensive readiness characterized by optimism, adaptability, and strategic engagement. Institutional support also plays a critical role in facilitating psychological competence development. The study contributes to vocational education literature by emphasizing the combined importance of resilience and career orientation in preparing trainees for workforce demands. Recommendations include integrating resilience training and career guidance into vocational programs to enhance holistic career readiness.